Does Responsiveness Dimensions Play the Key Role in Shaping Patient Satisfaction in Public Hospitals? - Adriel Fauzana; Akbar Adhi Utama (Journal of Research in Social Science and Humanities, 2025)
This study investigates how Service Quality Dimensions influence patient satisfaction in a public hospital setting, using Syarif Hidayatullah Hospital as a case study. Employing the Service Quality Model, five dimensions, such as Tangibility, Reliability, Responsiveness, Assurance, and Empathy, were analyzed through a Mixed-Method approach that combined quantitative survey data from 120 respondents with qualitative feedback using NVivo Software. The results indicated that Responsiveness, particularly in pharmacy services, was the most influential factor affecting patient satisfaction but also the weakest in performance. Descriptive and inferential statistics showed significant delays in prescription fulfillment, especially for Mixed and Concoction types, with average waiting times exceeding 30 minutes. Qualitative themes further revealed dissatisfaction related to communication breakdowns, lack of queue transparency, and insufficient updates during pharmacy processes. While Empathy and Assurance received high ratings, they could not compensate for operational inefficiencies that shaped patients’ final impressions. The study concludes that enhancing Responsiveness through workflow redesign, digital queue systems, and real-time communication tools is critical to improving overall satisfaction. These findings contribute to healthcare service improvement by emphasizing the strategic role of Responsiveness in public hospital environments.